Jurassic Marine Crocodiles in the Monts d’Ardèche UNESCO Global Geopark - Bernard Riou; Mehdi Bennourine; Nicolas Klee; Marc Lutz (Geoconservation Research)
Located in France on the eastern edge of the Massif Central, the Parc naturel regional des Monts d’Ardèche, inscribed as a UNESCO Global Geopark in 2014, presents great geological diversity. This includes a sedimentary boundary between the Jurassic and Cretaceous, represented by limestone and marl. Fossils of crocodilians have been discovered in these layers, highlighting the diversity of past marine environments. Sites of interest and their fossils are today protected and valorized by different public and private actors working in synergy, notably through the UNESCO Global Geopark label.